Coupling Biocompatible Au Nanoclusters and Cellulose Nanofibrils to Prepare the Antibacterial Nanocomposite Films - Wang, Peng; Yin, Baishuang; Dong, Huiling; Zhang, Yibo; Zhang, Yangheng; Chen, Rixin; Yang, Zukun; Huang, Caoxing; Jiang, Qing (Frontiers in Bioengineering and Biotechnology, 2020)
Cellulose nanofibrils (CNF) is considered as an inexhaustible precursor to produce antibacterial materials, such as antibacterial hydrogel, antibacterial paper, and antibacterial film. However, the poor antimicrobial property of neat CNF required it should be coupled with an antibacterial ingredient. Herein, biocompatible Au nanoclusters (AuNCs) were synthesized and added into the CNF dispersion to prepare a novel antibacterial film (AuNCs@CNF film). The effects of addition of AuNCs with different amount on the morphology and physicochemical properties of AuNCs@CNF films were characterized using atomic force microscopy (AFM), scanning electron microscopy (SEM), X-ray diffraction (XRD), FTIR (Fourier-transform infrared), light transmittance spectra, and thermogravimetric analysis (TGA). The results showed that AuNCs did not affect the nano-structural features of the CNF film and its basic structures, but could greatly increase the hydrophilicity, the flexibility and the thermal stability of CNF film, which might improve its application in antimicrobial wound-healing dressing. The prepared AuNCs@CNF films demonstrated high antibacterial properties toward Escherichia coli (E. coli) and Streptococcus mutans (S. mutans) both in vitro and in vivo, which can prohibit their growths and promote the healing of bacteria-infected wound, respectively. Thus, the prepared AuNCs@CNF film with great antibacterial properties could be applicable in biomedical field.